Relating Urban Biodiversity to Human Health With the ‘Holobiont’ Concept - Mills, Jacob G.; Brookes, Justin D.; Gellie, Nicholas J. C.; Liddicoat, Craig; Lowe, Andrew J.; Sydnor, Harrison R.; Thomas, Torsten; Weinstein, Philip; Weyrich, Laura S.; Breed, Martin F. (Frontiers in Microbiology, 2019)
A relatively unaccounted ecosystem service from biodiversity is the benefit to human health via symbiotic microbiota from our environment. This benefit occurs because humans evolved alongside microbes and have been constantly exposed to diverse microbiota. Plants and animals, including humans, are organised as a host with symbiotic microbiota, whose collective genome and life history form a single holobiont. As such, there are interdependencies between biodiversity, holobionts, and public health which lead us to argue that human health outcomes could be improved by increasing contact with biodiversity in an urban context. We propose that humans, like all holobionts, likely require a diverse microbial habitat to appropriate resources for living healthy, long lives. We discuss how industrial urbanisation likely disrupts the symbiosis between microbiota and their hosts, leading to negative health outcomes. The industrialised urban habitat is low in macro and microbial biodiversity and discourages contact with beneficial environmental microbiota. These habitat factors, alongside diet, antibiotics, and others, are associated with the epidemic of non-communicable diseases in these societies. We suggest that restoration of urban microbial biodiversity and micro-ecological processes through microbiome rewilding can benefit holobiont health and aid in treating the urban non-communicable disease epidemic. Further, we identify research gaps and some solutions to economic and strategic hurdles in applying microbiome rewilding into daily urban life.